An Assessment of The Effect of Training Practices on Staff Performance: A Case of The University of The Gambia - Zahra Jobe, Fatoumata; Njie, Matarr (Archives of Business Research, 2023)
The purpose of this paper is to assess the effect of training practices on the performance of the staffs of the University of the Gambia (UTG). A stratified sampling technique was used together with various other methods, including a mixed research approach, using both quantitative and qualitative research to assess the effect of training on staff performance. Primary data was collected from the UTG Human Resources Department and from the academic and administrative members of staff selected from all the Schools of the University, using semi-structured interviews and questionnaires. The quantitative data was gathered using the 5-point Likert scale items, and this was analyzed using Excel. The results of the study were presented together with its interpretation, using tables, pie charts and bar graphs. The findings of the study indicated that on-the job training is widely practised in the University of the Gambia. However, the process of staff training was found to be unplanned and unsystematic. It was further gathered that there is a lack of commitment from the senior management team regarding staff training. Overall, the findings of the study revealed that the training provided in University of the Gambia has not helped them realize any significant improvement in their work performance. These findings are contrary to the general consensus in the literature, which contend that training in fact does help improve staff performance. Nevertheless, taking these findings of the study into consideration, it is recommended that the University of the Gambia need to endeavor to set aside funds solely dedicated for training staffs on a continuous basis. The key recommendation will be to revise its current staff training and development policy to make training more effective.